2019
DOI: 10.1302/1863-2548.13.180185
|View full text |Cite
|
Sign up to set email alerts
|

Complex spine deformities in young patients with severe osteogenesis imperfecta: Current concepts review

Abstract: The severity of osteogenesis imperfecta (OI), the associated reduced quality and quantity of collagen type I, the degree of bone fragility, ligamentous laxity, vertebral fractures and multilevel vertebral deformities all impair the mechanical integrity of the whole spinal architecture and relate to the high prevalence of progressive kyphoscoliotic deformities during growth. Bisphosphonate therapy may at best slow down curve progression but does not seem to lower the prevalence of deformities or the incidence o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 57 publications
0
11
0
Order By: Relevance
“…The effect of underlying osteogenesis imperfecta on the cervical spine includes basilar invagination, atlantoaxial instability, and fractures of the cervical spine [8] . However, cervical spine fractures are rare [8] , and although dens, C2 pars, hangman and subaxial compression fractures have been reported during growth periods [8] , to the authors’ knowledge, there are no cases in the literature of such a severe cervical kyphosis at such a young age. This patient had a fracture through the posterior elements of C2 which was difficult to diagnose definitively on the initial imaging, but was easier to visualise on follow-up radiographs, once there was some evidence of healing.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The effect of underlying osteogenesis imperfecta on the cervical spine includes basilar invagination, atlantoaxial instability, and fractures of the cervical spine [8] . However, cervical spine fractures are rare [8] , and although dens, C2 pars, hangman and subaxial compression fractures have been reported during growth periods [8] , to the authors’ knowledge, there are no cases in the literature of such a severe cervical kyphosis at such a young age. This patient had a fracture through the posterior elements of C2 which was difficult to diagnose definitively on the initial imaging, but was easier to visualise on follow-up radiographs, once there was some evidence of healing.…”
Section: Discussionmentioning
confidence: 99%
“…The infant continues to be managed in the collar, pending further follow-up. The literature suggests that most cervical spine fractures in children with osteogenesis imperfecta heal well with external support, such as a rigid cervical collar or Halo body jacket [8] .…”
Section: Discussionmentioning
confidence: 99%
“…Other craniocervical abnormalities, such as basilar invagination (BI), are associated with OI ( Sillence, 1994 ). Sillence (1994) reported BI in 25% of subjects with OI type IV and Castelein et al (2019) reported BI in 13% of OI patients, with OI type III being the most common (39%). In our group of type 5 OI patients, we did not identify any BI.…”
Section: Discussionmentioning
confidence: 97%
“…The interdisciplinary team approach as described is especially indicated in the management of spinal disorders in OI. Progressive scoliosis, cranio-cervical deformities, and spondylolisthesis are the most common spine deformities in OI for which ample experience and training is needed (Wallace et al 2017, Castelein et al 2019. One of the indications for scoliosis surgery is to prevent deterioration of lung function.…”
Section: Discussionmentioning
confidence: 99%